Peran Teknologi Disruptif dalam Transformasi Perbankan dan Keuangan Islam di Indonesia - Nugraheni Fitroh Rezqi Syakarna (Universitas Muhammadiyah Ponorogo, 2023)
Disruptive technologies, which include innovations such as artificial intelligence (AI), blockchain technology, big data, and cloud computing, have significantly changed the landscape of the financial industry. However, in the context of Islamic banking and finance, the role of disruptive technologies in facilitating transformation is not fully understood. The results of this study show that disruptive technologies have great potential to transform Islamic banking and finance. The existence of blockchain technology can increase transparency, security, and accountability in Islamic financial transactions. Meanwhile, AI and big data can be used for risk analysis, portfolio management, and personalization of Islamic financial services. However, there are several challenges that need to be overcome before adopting disruptive technologies in the Islamic banking and finance sector. These challenges include the need for a clear legal framework for technology-based Islamic financial transactions, an imbalance of technological skills among Islamic finance practitioners, and concerns about data security and privacy. To optimize the role of disruptive technology in the transformation of Islamic banking and finance, strategic steps are needed. Governments, regulators, and Islamic financial institutions need to work together to create an adequate and supportive legal framework for the adoption of disruptive technologies. In addition, training and the development of technology skills need to be increased among Islamic finance practitioners. Furthermore, cooperation between Islamic financial institutions and fintech technology can encourage innovation that is relevant to the principles of Islamic finance.